Doing criticism across literary and screen arts - Chandler, James 1948- (John Wiley & Sons, Inc., 2022)
"In Doing Criticism: Across Literary and Screen Arts, renowned scholar James Chandler teaches readers how to engage actively and productively with a critical object, whether a poem, a novel, a film, a play, or a television series. Updating and broadening an older understanding of 'practical criticism' for our own moment, Chandler show students at all levels how to ask the right questions and how to pursue those questions effectively. This is an invaluable book that not only explains what makes criticism interesting and compelling but also offers concrete illustrations of what it looks like on the page. It argues that doing without criticism is not only unwise, but perhaps simply impossible." --Back cover.